Preparation method of nano color paste for colored concrete

Through high-pressure homogeneity treatment and emulsion polymerization and wrapping technology, nano-color paste for nano-sized colored concrete is formed, which solves the problem of poor dispersion of nanopigments and improves the compactness and compressive resistance of concrete.

CN119774910AActive Publication Date: 2025-04-08明光科迪纳微新材料股份有限公司
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510264737.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-08
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

The nanopigments in existing colored concrete have poor dispersion and are prone to react with concrete components, resulting in protection failure, and adding dispersant may lead to excessive bubbles, affecting the compactness of the concrete.

Method used

The nano-inorganic pigment is treated with high pressure homogenization to form a fine emulsion, mixed with an acrylic solution, and emulsion polymerization and encapsulation are carried out using ultrasonic treatment and a low-temperature redox initiator to form a nano-color paste.

Benefits of technology

The dispersion of nanopigments is improved, the nano-sized particles are maintained, the compatibility between the nano-color paste and concrete is enhanced, and the compactness and compressive resistance of the concrete are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of nano color paste for colored concrete, and belongs to the technical field of dye preparation. The preparation method comprises the following steps: mixing a nano inorganic pigment miniemulsion and an acrylic acid solution according to a weight part ratio of 1: (1-2), carrying out 200-300W ultrasonic power treatment for 5-10min to obtain a mixed emulsion, mixing the mixed emulsion and a redox initiator according to a weight part ratio of 1: (0.002-0.005), and carrying out ultrasonic treatment for 5-10min to obtain a mixed emulsion; and carrying out polymerization treatment for 3-5 hours in a temperature environment of 40-50 DEG C to obtain the nano color paste for the colored concrete. The preparation method comprises the following steps: firstly, carrying out high-pressure homogenization treatment on a nano inorganic pigment to obtain a nano inorganic pigment miniemulsion, and then coating the nano inorganic pigment through emulsion polymerization to form the nano color paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dye preparation, and in particular relates to a method for preparing nano color paste for colored concrete. Background Art

[0002] With the sustained, stable and rapid development of my country's economy, a large number of infrastructure constructions are underway. Concrete has become one of the most widely used building materials due to its advantages of being non-toxic, odorless, high-strength, durable and easy to shape. Its application has spread to many fields such as civil engineering, urban construction, and transportation. However, since most concrete appears in people's vision with a single color and a gray and cold color, with the progress of modern society and the increasing improvement of people's living tastes, people's requirements for the material environment are no longer just to meet its practicality, but more attention is paid to the pursuit of its artistic visual effects. In the fields of urban construction and transportation, higher requirements are put forward for the decoration of buildings and the beautification and induction of highway infrastructure. Large buildings and structures are basically made of concrete, and their appearance is cold and single. In order to make them have a certain aesthetic effect and naturally coordinate with the surrounding environment to achieve a certain aesthetic effect, the most commonly used method at present is to decorate them again, such as painting their exterior. Painting requires building a workbench outside the built building, which is inconvenient. In addition, many exterior decoration materials are polluted. After long-term exposure to the sun and rain, they are prone to fading and peeling. The cost of maintenance and repair is expensive and the process is cumbersome. Against this background, a new type of decorative concrete, colored concrete, came into being. The use of colored concrete can effectively solve these problems: on the one hand, the decorativeness of colored concrete can greatly enrich the color of the building, easily obtain natural and elegant building finishes, and achieve the expected aesthetic effect more easily; on the other hand, the one-time construction of colored concrete can obtain the decorative effect, which reduces the secondary decoration of the building. It can not only save a lot of resources and reduce environmental pollution, but also has the advantages of fast construction and good durability. With the country's vigorous promotion of resource conservation and building energy conservation, the application of colored concrete in the construction field has received more and more attention.

[0003] The coloring of colored concrete is mainly achieved by adding pigments. The type and quality of pigments directly affect the color effect and performance of concrete. According to the properties of pigments, they can be mainly divided into the following categories: (1) Inorganic pigments: Inorganic pigments refer to pigments made from inorganic compounds. They are often used in colored concrete. Their main advantages include good light stability and will not fade after long-term exposure to sunlight; they are not easy to undergo chemical reactions under various environmental conditions, and can maintain long-term color stability and high chemical stability; environmental protection: most inorganic pigments are non-toxic and non-volatile, meeting environmental protection requirements; (2) Organic pigments: Organic pigments are pigments made from organic compounds and usually have bright colors. Their main advantages include providing more diverse and bright colors and are widely used in occasions that require specific color effects. However, organic pigments have relatively poor light resistance and durability, are not as stable as inorganic pigments, and have a higher impact on the environment than inorganic pigments.

[0004] Patent CN103275561B discloses an environmentally friendly water-based nano-color paste and its preparation method. The invention adds a dispersant, a sterilizer, a barrier agent and a water-based pigment, and then uses a physical grinding method to make it reach the nanometer level. Patent CN107603347B discloses a water-based nano-color paste dispersant and its preparation method. The invention uses cyclodextrin and oleic acid with good biocompatibility as raw materials, and then cooperates with a suitable surfactant to prepare a super-dispersible water-based nano-color paste dispersant through thermal initiation polymerization, and then mixes it with the ground pigment to obtain a water-based nano-color paste. Patent CN114163875B discloses a red nano-color paste and its preparation method and application. The invention first acid-washes the red pigment to obtain an acid-treated pigment, then mixes the acid-treated pigment with sodium chloride and an organic solvent for salt milling to obtain a salt-milled pigment, and then mixes the salt-milled pigment with an acrylate monomer, a dispersant, a stabilizer and a synergistic dispersant for ball milling to obtain a red nano-color paste. The above-mentioned nano-color pastes need to add dispersants during preparation to prevent the agglomeration of nano-particle pigments. However, due to the special alkaline environment of concrete, the dispersant is easy to react with the components in the concrete, which causes the dispersant to lose its protection for the nano-pigment. If the amount of dispersant used is further increased, it may cause adverse effects such as excessive bubbles, increase the porosity of the concrete, and have a greater impact on the density of the concrete.

[0005] Therefore, designing a nano-color paste that can improve the dispersibility of nano-pigment is of great significance for the preparation of colored concrete. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention firstly obtains a nano inorganic pigment fine emulsion by high pressure homogenization treatment of the nano inorganic pigment, and then forms a nano color paste by encapsulating the nano inorganic pigment through emulsion polymerization, thereby solving the technical problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents: A method for preparing nano-color paste for colored concrete, the preparation method comprising the following steps: The nano inorganic pigment fine emulsion and the acrylic acid solution are mixed in a weight ratio of 1:1-2 and subjected to an ultrasonic power treatment of 200-300 W for 5-10 min to obtain a mixed emulsion, the mixed emulsion is mixed with a redox initiator in a weight ratio of 1:0.002-0.005, and subjected to a polymerization treatment in a temperature environment of 40°C-50°C for 3-5 h to obtain the nano color paste for colored concrete.

[0007] Furthermore, the preparation method of the nano inorganic pigment miniemulsion comprises the following steps: The nano inorganic pigment is dispersed in anhydrous ethanol to form a dispersed phase, an anionic surfactant is dissolved in deionized water to form an aqueous phase, the dispersed phase and the aqueous phase are mixed in a weight ratio of 1:3-5 and then subjected to high pressure homogenization to obtain the nano inorganic pigment miniemulsion.

[0008] Furthermore, the nano inorganic pigment includes nano titanium dioxide or nano ferrosoferric oxide, and the particle size of the nano inorganic pigment is 10-20 nm.

[0009] Furthermore, the weight ratio of the nano inorganic pigment to anhydrous ethanol is 1:10-15.

[0010] Furthermore, the anionic surfactant includes sodium stearate or sodium oleate.

[0011] Furthermore, the weight ratio of the anionic surfactant to deionized water is 1:30-40.

[0012] Furthermore, the conditions of the high-pressure homogenization include a pressure of 70-80 MPa and a processing time of 12-15 min.

[0013] Furthermore, the mass concentration of the acrylic acid solution is 40-60%.

[0014] Furthermore, the redox initiator is composed of ammonium persulfate and sodium bisulfite in a molar ratio of 1-2:1.

[0015] A nano color paste for colored concrete is prepared by a method for preparing a nano color paste for colored concrete.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses nano inorganic pigments of a specific particle size as one of the core raw materials of nano color paste, pre-treats it into nano inorganic pigment fine emulsion by high pressure homogenization, and then ultrasonically treats the nano inorganic pigment fine emulsion and acrylic acid solution, and utilizes the low temperature redox initiation mechanism to enable the nano inorganic pigment to be polymerized and wrapped by acrylic acid monomer in the emulsion system, thereby synthesizing nano color paste with nano size. Compared with conventional emulsion, the nano inorganic pigment fine emulsion treatment can form smaller droplets, prevent the nano inorganic pigments in the emulsion from attracting each other and further forming larger particles, which is beneficial to the dispersion of the nano inorganic pigment. At this time, the low temperature redox initiation constructed by ammonium persulfate and sodium bisulfite is used to carry out polymerization reaction, and the pre-treated fine emulsion is combined with the low temperature redox initiation process, while solving the dispersibility of the nano inorganic pigment, the particles in the nano color paste obtained by polymerization can also maintain a good nano size, and the polyacrylic acid structure formed by the polymerization of acrylic acid monomer has good hydrophilicity, which can increase the compatibility of the nano color paste with concrete. DETAILED DESCRIPTION

[0017] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0018] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0019] The nano-ferroferric oxide has an average particle size of 10-20 nm and is purchased from Hangzhou Hengna New Materials Co., Ltd. Nano-grade titanium dioxide with an average particle size of 10-20 nm was purchased from Shanghai Liangjiang Titanium Dioxide Chemical Products Co., Ltd. PCA ® -I Polycarboxylate high-efficiency water reducer was purchased from Jiangsu Subot New Materials Co., Ltd.; The silicate cement with strength grade PO 42.5 was purchased from Tangshan Hongye Special Cement Co., Ltd.

[0020] Preparation Example 1: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: Weigh 1 part by weight of nano-grade titanium dioxide powder with an average particle size of 10 nm and add it to 10 parts by weight of anhydrous ethanol, and then disperse it under 100W ultrasonic power for 20 minutes to obtain a dispersed phase. Dissolve 1 part by weight of anionic surfactant sodium stearate in 30 parts by weight of deionized water to form an aqueous phase (heating can be used to promote dissolution), take 1 part by weight of the dispersed phase and 3 parts by weight of the aqueous phase, mix them, and then put them into a high-pressure homogenizer, control the pressure to 70MPa, and homogenize for 12 minutes to obtain a nano inorganic pigment miniemulsion.

[0021] Preparation Example 2: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-grade titanium dioxide powder with an average particle size of 10 nm was weighed and added to 11 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium stearate was dissolved in 32 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase and 3 parts by weight of the aqueous phase were mixed, and then placed in a high-pressure homogenizer, the pressure was controlled to 70 MPa, and the nano-inorganic pigment fine emulsion was obtained by homogenization treatment for 13 minutes.

[0022] Preparation Example 3: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-grade titanium dioxide powder with an average particle size of 10 nm was weighed and added to 12 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium stearate was dissolved in 34 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 4 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 75 MPa, and the nano-inorganic pigment fine emulsion was obtained by homogenization treatment for 13 minutes.

[0023] Preparation Example 4: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 20 nm was weighed and added to 13 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium oleate was dissolved in 36 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 4 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 75MPa, and the nano-inorganic pigment miniemulsion was obtained by homogenization treatment for 14 minutes.

[0024] Preparation Example 5: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 20 nm was weighed and added to 14 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium oleate was dissolved in 38 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 5 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 80MPa, and the nano-inorganic pigment miniemulsion was obtained by homogenization treatment for 14 minutes.

[0025] Preparation Example 6: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 20 nm was weighed and added to 15 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium oleate was dissolved in 40 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 5 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 80MPa, and the nano-inorganic pigment miniemulsion was obtained by homogenization treatment for 15 minutes.

[0026] Preparation Example 7: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 50 nm was weighed and added to 15 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium oleate was dissolved in 40 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 5 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 80MPa, and the nano-inorganic pigment miniemulsion was obtained by homogenization treatment for 15 minutes.

[0027] Preparation Example 8: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 20 nm was weighed and added to 15 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of cationic surfactant hexadecyltrimethylammonium chloride was dissolved in 40 parts by weight of deionized water to form an aqueous phase (dissolution can be promoted by heating), 1 part by weight of the dispersed phase was mixed with 5 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 80MPa, and the nano-inorganic pigment fine emulsion was obtained by homogenization treatment for 15 minutes.

[0028] Preparation Example 9: The preparation method of nano inorganic pigment miniemulsion comprises the following steps: 1 part by weight of nano-iron tetroxide powder with an average particle size of 20 nm was weighed and added to 15 parts by weight of anhydrous ethanol, and then subjected to 100W ultrasonic power dispersion treatment for 20 minutes to obtain a dispersed phase. 1 part by weight of anionic surfactant sodium oleate was dissolved in 40 parts by weight of deionized water to form an aqueous phase (heating can be used to promote dissolution), 1 part by weight of the dispersed phase was mixed with 5 parts by weight of the aqueous phase, and then placed in a high-pressure homogenizer, the pressure was controlled to 90MPa, and the nano-inorganic pigment miniemulsion was obtained by homogenization treatment for 20 minutes. Example 1

[0029] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 1 and 1 part by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 40%), mix and stir, then adjust the ultrasonic power to 200 W, start ultrasonic treatment for 5 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 1:1) according to 0.004 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 40°C for polymerization treatment for 3 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete. Example 2

[0030] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 2 and 1.2 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 40%), mix and stir, then adjust the ultrasonic power to 200 W, start ultrasonic treatment for 6 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 1:1) according to 0.006 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 40°C for polymerization treatment for 3 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete. Example 3

[0031] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 3 and 1.4 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 50%), mix and stir, then adjust the ultrasonic power to 250W, start ultrasonic treatment for 7 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 1.5:1) according to 0.006 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 45°C for polymerization treatment for 4 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete. Example 4

[0032] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 4 and 1.6 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 50%), mix and stir, then adjust the ultrasonic power to 250W, start ultrasonic treatment for 8 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 1.5:1) according to 0.008 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 45°C for polymerization treatment for 4 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete. Example 5

[0033] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 5 and 1.8 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 60%), mix and stir, then adjust the ultrasonic power to 300 W, start ultrasonic treatment for 9 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 2:1) according to 0.008 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 50°C for polymerization treatment for 5 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete. Example 6

[0034] A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 6 and 2 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 60%), mix and stir, then adjust the ultrasonic power to 300 W, start ultrasonic treatment for 10 minutes to obtain a mixed emulsion, add a redox initiator composed of ammonium persulfate and sodium bisulfite (the molar ratio of ammonium persulfate: sodium bisulfite is 2:1) according to 0.01 times the weight of the mixed emulsion, mix, use nitrogen as a protective gas, and then heat to 50°C for polymerization treatment for 5 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete.

[0035] Comparative Example 1: A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: The nano inorganic pigment miniemulsion in Example 4 was replaced by the nano inorganic pigment miniemulsion obtained in Preparation Example 7, and the other conditions remained the same as in Example 4.

[0036] Comparative Example 2: A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: The nano inorganic pigment miniemulsion in Example 4 was replaced by the nano inorganic pigment miniemulsion obtained in Preparation Example 8, and the other conditions remained the same as in Example 4.

[0037] Comparative Example 3: A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: The nano inorganic pigment miniemulsion in Example 4 was replaced by the nano inorganic pigment miniemulsion obtained in Preparation Example 9, and the other conditions remained the same as in Example 4.

[0038] Comparative Example 4: A method for preparing nano-color paste for colored concrete, specifically comprising the following steps: Weigh 1 part by weight of the nano inorganic pigment fine emulsion obtained in Preparation Example 4 and 1.6 parts by weight of acrylic acid solution (the mass concentration of the acrylic acid solution is 50%), mix and stir, then adjust the ultrasonic power to 250W, start ultrasonic treatment for 8 minutes to obtain a mixed emulsion, add ammonium persulfate according to 0.008 times the weight of the mixed emulsion, use nitrogen as a protective gas, and then heat to 60°C for polymerization treatment for 4 hours. After the polymerization reaction is completed, naturally cool to room temperature to obtain a nano color paste for colored concrete.

[0039] The nano-color pastes for colored concrete prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were diluted 1000 times with deionized water to obtain samples 1 to 10, and then the particle sizes of samples 1 to 10 were measured using a particle size analyzer at a temperature of 25° C. The results are shown in Table 1 below.

[0040] Table 1 Particle size test

[0041] Take 25kg of ordinary Portland cement (strength grade is PO 42.5), 71kg of river sand, 110kg of crushed stone (particle size controlled at 5~20mm), 13kg of water, 1kg of water reducer (PCA ® -I polycarboxylate high-efficiency water-reducing agent) and 3.75kg of colored concrete nano-color paste were mixed and stirred to form concrete, and then prepared into a 150mm×150mm×150mm cubic standard compressive test piece. The molding and curing of the test piece were in accordance with "Chapter 2 Preparation and Curing of Test Pieces" in "GBJ81-85". The test piece was cured to 28 days of age, and then tested with a 1000kN pressure testing machine. The test loading speed was controlled in the range of 0.4~0.5MPa / s. The compressive strength was obtained by testing. The results are shown in Table 2 below.

[0042] Table 2 Concrete compressive strength values ​​on the 28th day

[0043] The following conclusions can be drawn from the test results in Table 1 and Table 2: (1) It can be found from Examples 1 to 6 that the present invention first obtains a nano inorganic pigment fine emulsion with a specific particle size of nano inorganic pigment by high-pressure homogenization, and then forms a nano color paste for colored concrete by emulsion polymerization and encapsulation through a low-temperature redox-initiated polymerization system. This type of emulsion polymerization encapsulation can improve the dispersion performance of the nano inorganic pigment and achieve a good nano size. The prepared concrete has good compressive performance.

[0044] (2) It can be found from Comparative Example 1 that by further increasing the particle size of nano-ferroferric oxide, the particle size of the nano-color paste obtained after polymerization is 136.6nm, which does not meet the size of nano-materials. This may be because the reaction conditions in this system are not suitable for larger nano-inorganic pigments, which leads to a further increase in the particle size of the emulsion after the polymerization reaction. In addition, due to the increase in particle size, the density of concrete is deteriorated and the porosity is higher when preparing concrete, resulting in poor compressive performance of concrete.

[0045] (3) It can be found from Comparative Example 2 that due to the oxide functional groups on the surface of nano-ferroferric oxide, when mixed with the aqueous phase, it interacts with water molecules, resulting in a negative charge on the surface, while the surface active ions generated by the cationic surfactant when it dissociates in contact with the aqueous phase are mainly positively charged. The electrostatic attraction between the positive charge and the surface negative charge of the nano-ferroferric oxide may lead to the aggregation of particles, which is not conducive to dispersion, so that the particle size of the nano-color paste for colored concrete finally prepared is 203.1nm, which exceeds the nanometer size. In addition, due to the increase in particle size, the compactness of the concrete is deteriorated and the porosity is high when preparing the concrete, resulting in poor compressive performance of the concrete.

[0046] (4) It can be found from Comparative Example 3 that in this system, the particle size of the prepared colored concrete nano-color paste is 187.3 nm by further increasing the pressure and time during the high-pressure homogenization process. This may be due to the excessively high pressure homogenization pressure and the excessively long high-pressure homogenization treatment time, which may destroy the active structure of the anionic surfactant, resulting in the weakening of the anionic surfactant's ability to disperse the nano inorganic pigment, and then leading to the aggregation of the nano inorganic pigment. As a result, the particle size of the finally prepared colored concrete nano-color paste is larger, exceeding the nano size, and the increase in particle size may lead to poor compactness and high porosity during the preparation of concrete, resulting in poor compressive performance of the concrete.

[0047] (5) It can be found from Comparative Example 4 that in this system, ammonium persulfate is used alone as an initiator. Ammonium persulfate-induced polymerization requires a relatively high temperature to carry out a thermally initiated polymerization reaction. The thermal initiation temperature is relatively high, and the initiation activation energy is high, resulting in a relatively high conversion efficiency of the monomers in the polymerization reaction, which may lead to rapid growth of the polymer chain, and then cause the particles to aggregate with each other in the emulsion to form particles with larger particle sizes. In addition, due to the increase in particle size, the compactness of the concrete may be deteriorated when preparing the concrete, and the porosity may be relatively high, resulting in poor compressive performance of the concrete. Therefore, in the system of the present invention, there are relatively strict requirements for the use of initiators.

[0048] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing nano-color paste for colored concrete, characterized in that: The preparation method comprises the following steps: The nano inorganic pigment fine emulsion and the acrylic acid solution are mixed in a weight ratio of 1:1-2 and subjected to an ultrasonic power treatment of 200-300W for 5-10 minutes to obtain a mixed emulsion, and the mixed emulsion is mixed with a redox initiator in a weight ratio of 1:0.002-0.005, and subjected to a polymerization treatment in a temperature environment of 40°C-50°C for 3-5 hours to obtain the nano color paste for colored concrete; The preparation method of the nano inorganic pigment miniemulsion comprises the following steps: The nano inorganic pigment is dispersed in anhydrous ethanol to form a dispersed phase, an anionic surfactant is dissolved in deionized water to form an aqueous phase, the dispersed phase and the aqueous phase are mixed in a weight ratio of 1:3-5 and then subjected to high pressure homogenization to obtain the nano inorganic pigment miniemulsion; The conditions of the high-pressure homogenization include a pressure of 70-80 MPa and a processing time of 12-15 min.

2. The method for preparing a nano-color paste for colored concrete according to claim 1, characterized in that: The nano inorganic pigment includes nano titanium dioxide or nano ferrosoferric oxide, and the average particle size of the nano inorganic pigment is 10-20 nm.

3. The method for preparing a nano-color paste for colored concrete according to claim 1, characterized in that: The weight ratio of the nano inorganic pigment to anhydrous ethanol is 1:10-15.

4. The method for preparing a nano-color paste for colored concrete according to claim 1, characterized in that: The anionic surfactant includes sodium stearate or sodium oleate.

5. The method for preparing a nano-color paste for colored concrete according to claim 1, characterized in that: The weight ratio of the anionic surfactant to deionized water is 1:30-40.

6. The method for preparing a nano-color paste for colored concrete according to claim 1, characterized in that: The mass concentration of the acrylic acid solution is 40-60%.

7. The method for preparing nano-color paste for colored concrete according to claim 1, characterized in that: The redox initiator is composed of ammonium persulfate and sodium bisulfite in a molar ratio of 1-2:

1.

8. A nano-color paste for colored concrete prepared by the method for preparing a nano-color paste for colored concrete according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Environmentally-friendly water-based nanometer color paste and preparation method thereof

    CN103275561B

  • Aqueous nano-color paste dispersant and its preparation method

    CN107603347B

  • Red Nanoparticle Colorant, its Preparation Method and Application

    CN114163875B

  • Method for preparing colorful polystyrene particle synthesized by in-situ suspension polymerization one-step process

    CN101633709A

  • Three-layer core-shell-structure inorganic nanoparticle / silicon dioxide / high polymer composite microspheres and preparation method thereof

    CN102344632A